Knowledge, Attitude, Practices and Factors Affecting Fruit and Vegetable Consumption in Adolescents (Gokwe South District) - Makumbe, Brighton (Midlands State University, 2017)
Fruits and vegetable consumption pattern and its factors among adolescents in Gokwe South District were determined. The study drew participants from 2 schools, one from rural settlements and the other from the urban site. A total of 80 participants took part in the stud.40 participants were randomly selected from each participating school. A food frequent questionnaire, a 24-hour recall and KAP questionnaire were used to collect data from the participants. The study indicated a low fruit and vegetable intake among adolescents. Fruits recorded mean servings of 1.1125 per day which is below the required minimum of 2 servings per day. Vegetable recorded a mean serving of 1.325 which is much lower than the minimum recommended servings of 3 per day. The findings indicated vegetable consumption to vary with attitude; home availability of fruits and vegetables and geographical location. Knowledge, availability of fruits and vegetables, geographical location and socioeconomic status all indicated to affect fruit consumption. The findings also show that adolescents have poor knowledge on the recommended intake of fruits and vegetables.